THE TABORIC LIGHT IN THE HYMNS OF THE VESPERS OF THE TRANSFIGURATION FEAST. CATECHETIC CONSIDERATIONS - VIDICAN-MANCI, Liviu (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2020)
Man’s purpose, by his own nature, is deification; he is called to mysteriously become god through his free collaboration with the grace of the Holy Spirit. In other words, man must partake in the radiance of godly glory and become a light similar to the One Who is Light and the source of Light. This calling is underlined many times in the writings of the mystics who experienced the becoming into light. The transfer of these mystical experiences can be found in a catechetic form in the liturgical rites gravitating around the feast of the Lord’s Transfiguration. The content of these odes helps us understand that the partaking in the light radiating from the Being of the Trinity is not a request reserved only for those initiated in the Hesychastic life, but an offer made to all Christians who take part in Eucharistic life. They mysteriously rejoice at their partaking in the mystical Body of Jesus Christ. This suggests that actually living in the light of God’s glory is a sine qua non condition for salvation.